2007
DOI: 10.1353/hub.2007.0022
|View full text |Cite
|
Sign up to set email alerts
|

Association of PPARG2 Pro12Ala Variant with Larger Body Mass Index in Mestizo and Amerindian Populations of Mexico

Abstract: Previous studies have sought to associate the Pro12Ala variant of the peroxisome proliferator-activated receptor gamma2 (PPARG2) gene with type 2 diabetes, insulin resistance, and obesity, with controversial results. We have determined the Pro12Ala variant frequency in 370 nondiabetic Mexican Mestizo subjects and in five Mexican Amerindian groups and have investigated its possible association with lipid metabolism, insulin serum levels, and obesity in three of these populations. Two independent case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
0
23
1
1
Order By: Relevance
“…Nevertheless, it has been shown that there is a strong correlation between genetic estimates obtained with sets of ancestry-informative markers and those obtained with high-density data in samples from Ibero-America (37,82). A large variation has been reported in the individual estimates of ancestry within the predefined ancestry categories (19,24,82). Although potentially informative, it is problematic to contrast this variation across published studies because of the large differences in the number of markers examined and the sampling strategies used.…”
Section: Genetic Ancestry In European Americans and African Americansmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been shown that there is a strong correlation between genetic estimates obtained with sets of ancestry-informative markers and those obtained with high-density data in samples from Ibero-America (37,82). A large variation has been reported in the individual estimates of ancestry within the predefined ancestry categories (19,24,82). Although potentially informative, it is problematic to contrast this variation across published studies because of the large differences in the number of markers examined and the sampling strategies used.…”
Section: Genetic Ancestry In European Americans and African Americansmentioning
confidence: 99%
“…Rather, these studies have mostly concentrated on either the United States or Ibero-America (i.e., the former Spanish and Portuguese colonies) in isolation. This literature also shows different research approaches in that population genetic studies of the United States have usually examined separately the genetic diversity of European Americans, African Americans, and Hispanics (19,24). By contrast, studies of Ibero-American countries usually examine the extent of Native American, European, and African ancestry without reference to perceived ancestry labels (84,85,87).…”
Section: Introductionmentioning
confidence: 99%
“…22 Interestingly, Amerindian populations (Mazahuas and Nahuas) exhibited the highest frequencies of the Ala12 allele (25%), which was in agreement with previous studies in Yaquis, Mayas, and Triquis. 23 Conversely, European (≤10%) and African (≤1%) ethnicities showed lower frequencies of Ala12 than in Mestizos and Amerindians. 18 Therefore, it is likely that Amerindian lineages could contribute to the development of MD.…”
Section: Discussionmentioning
confidence: 94%
“…One possible interaction pathway between them could be energy balance, where both genes play a critical role. 23,25 It is possible that this interaction requires the participation of other molecular mediators (transcription factors) since recent research has suggested that LYPLAL1 is not directly regulated by PPARG. 25 Another possibility could be that LYPLAL1 may act as other lipases (lysophospholipase I) modulating the biological activity of different proteins, which in turn are regulated by PPARG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation